(untitled) (Olhares, 2025)
The research dives into the vast universe of possibilities brought by the human experience. When crossing it, our perception, and the way we see ourselves in the world are profoundly affected. Experience acts as a link between the real and fictional worlds, a bridge that connects what is outside of us with what resides within everyone who connects to it. The question then arises: is it possible to experience a sense of belonging to the territory we inhabit after going through a performance experience? What do we see and feel on this journey influence our connection to the world? Could it be that even with an apparently limited repertoire of artistic influences, it is still possible to understand the world, art, and life? These questions underlie this article, seeking to establish connections that can guide us towards their answers. The research undertakes a meaningful quest, exploring the relationship between experience, perception, art, and life, in search of a deeper and more enlightening understanding.